2022
DOI: 10.1098/rspb.2021.2086
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of flexible biting in hyperdiverse parasitoid wasps

Abstract: One key event in insect evolution was the development of mandibles with two joints, which allowed powerful biting but restricted their movement to a single degree of freedom. These mandibles define the Dicondylia, which constitute over 99% of all extant insect species. It was common doctrine that the dicondylic articulation of chewing mandibles remained unaltered for more than 400 million years. We report highly modified mandibles overcoming the restrictions of a single degree of freedom and hypothesize their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…For species with two well-developed condyles, the location and orientation of may be identified with reasonable accuracy from joint morphology alone, as previously done for beetles [10, 142], cockroaches [82] and dragonflies [61]. Other insects such as some hymenopterans, however, have more complex mandible joints [144,145], which may also have more than one degree of freedom [89, 146, 147], rendering such deductions difficult [but see 119, Kang, Püffel and Labonte, in preparation]. Given the sensitivity of bite forces to the joint axis, it is surprising how little attention has been paid to rigorously determine joint kinematics across the insect tree of life using the tools of rigid body mechanics [but see 146, and Kang, Püffel and Labonte, in preparation].…”
Section: Resultsmentioning
confidence: 92%
“…For species with two well-developed condyles, the location and orientation of may be identified with reasonable accuracy from joint morphology alone, as previously done for beetles [10, 142], cockroaches [82] and dragonflies [61]. Other insects such as some hymenopterans, however, have more complex mandible joints [144,145], which may also have more than one degree of freedom [89, 146, 147], rendering such deductions difficult [but see 119, Kang, Püffel and Labonte, in preparation]. Given the sensitivity of bite forces to the joint axis, it is surprising how little attention has been paid to rigorously determine joint kinematics across the insect tree of life using the tools of rigid body mechanics [but see 146, and Kang, Püffel and Labonte, in preparation].…”
Section: Resultsmentioning
confidence: 92%
“…For species with two well-developed condyles, the location and orientation of may be identified with reasonable accuracy from joint morphology alone, as previously done for beetles [ 10 , 147 ], cockroaches [ 86 ] and dragonflies [ 61 ]. Other insects such as some hymenopterans, however, have more complex mandible joints [ 149 , 150 ], which may also have more than one degree of freedom [ 93 , 151 , 152 ], rendering such deductions difficult (but see [ 116 , 124 ]). Given the sensitivity of bite forces to the joint axis, it is surprising how little attention has been paid to rigorously determine mandible joint kinematics across the insect tree of life using the tools of rigid body mechanics (but see [ 116 , 151 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Barden and Perrichot with colleagues, on the basis of external morphology and the unique finding of Ceratomyrmex ellenbergeri with a captured prey, a nymph of Caputoraptor elegans , have come to conclusion that mandibles of these representatives « uniquely articulating in a vertical plane oblique to longitudinal axis of body, in addition to a moderate lateral opening» (Barden at al., 2020). Recently discovered and yet undescribed species Colotrechninae sp., a representative of Chalcidoidea, exhibits a striking external resemblance to Cretaceous Haidomyrmecinae in head structures (facial processes, elongated setae near the mouthparts), mandibular morphology (elongated, curved upwards) and their relative position (Van de Kamp et al, 2022). The study of the only specimen has revealed the presence of a single, specifically anterior, mandibular condyle that allows mandibles to articulate in different planes – vertical movements (holding objects between the head capsule and mandibles), also lateral movements (manipulations in the space between mandibles).…”
Section: Resultsmentioning
confidence: 99%